A novel marine nitrite-oxidizing Nitrospira species from Dutch coastal North Sea water - Haaijer, Suzanne C.; Ji, Ke; Van Niftrik, Laura; Hoischen, Alexander; Speth, Daan R.; Jetten, Mike S.; Sinninghe Damsté, Jaap S.; Op Den Camp, Huub J. (Frontiers in Microbiology, 2013)
Marine microorganisms are important for the global nitrogen cycle, but marine nitrifiers, especially aerobic nitrite-oxidizers, remain largely unexplored. To increase the number of cultured representatives of marine nitrite-oxidizing bacteria (NOB), a bioreactor cultivation approach was adopted to first enrich nitrifiers and ultimately nitrite oxidizers from Dutch coastal North Sea water. With solely ammonia as the substrate an active nitrifiying community consisting of novel marine Nitrosomonas aerobic ammonia oxidizers (AOB) and Nitrospina and Nitrospira NOB was obtained which converted a maximum of 2 mmoles of ammonia per liter per day. Switching the feed of the culture to nitrite as a sole substrate resulted in a Nitrospira NOB dominated community (approximately 80% of the total microbial community based on FISH and metagenomic data) converting a maximum of 3 mmoles of nitrite per liter per day. Phylogenetic analyses based on the 16S rRNA gene indicated that the Nitrospira enriched from the North Sea is a novel Nitrospira species with Nitrospira marina as the next taxonomically described relative (94% 16S rRNA sequence identity). Transmission electron microscopy analysis revealed a cell plan typical for Nitrospira species. The cytoplasm contained electron light particles that might represent glycogen storage. A large periplasmic space was present which was filled with electron dense particles. Nitrospira-targeted PCR analyses demonstrated the presence of the enriched Nitrospira species in a time series of North Sea genomic DNA samples. The availability of this new Nitrospira species enrichment culture facilitates further in-depth studies such as determination of physiological constraints, and comparison to other NOB species.